Chemical epitaxy of CdS on GaAs. Issue 7 (31st January 2017) - Friedman, Ofir; Upcher, Alexander; Templeman, Tzvi; Ezersky, Vladimir; Golan, Yuval
Abstract : Epitaxial thin films of CdS were deposited from solution onto GaAs(100) and GaAs(111)B. Abstract : We have studied the microstructure and crystallographic orientation of CdS films chemically deposited on GaAs substrates. CdS thin films deposited on GaAs(100) showed an oriented polycrystalline micro-structure. Depending on the duration and the temperature of the deposition, two out-of-plane orientations were obtained, with the (10.1) and (00.1) planes of the wurtzite CdS film aligned parallel to the GaAs substrate surface. While the orientation of CdS thin films on GaAs(100) substrate is highly sensitive to the deposition parameters, they do not affect the orientation obtained on GaAs(111)B substrates, which resulted exclusively in monocrystalline (00.1) oriented CdS films. In all three orientations above, a high density of stacking-faults was observed in the films. On the other hand, growth on GaAs(111)A substrate resulted in randomly oriented polycrystalline films. This work provides the first reported evidence for chemical epitaxy of CdS on GaAs.